2004
DOI: 10.1016/j.paid.2003.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of the thought suppression paradigm in explaining impulsivity and aggression

Abstract: This study investigated (1) the usefulness of the thought suppression paradigm in understanding impulsivity and aggression and (2) the relation between intrusions, suppression and other control strategies on the one hand, and psychopathology on the other. Ninety undergraduate students filled in the White Bear Suppression Inventory (WBSI), the Thought Control Questionnaire (TCQ), the Minnesota Multiphasic Personality Inventory-2 (MMPI-2), five traits from the Eysenck Personality Profiler (EPP), and the Barratt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…These findings are in line with the results of a study by Rassin and Diepstraten (2003) who found a positive correlation between TCQ-punishment and WBSI-total in a sample of obsessive compulsive disordered patients. Nagtegaal and Rassin (2004) reached the same conclusion in a student sample and also established a relation between intrusive thinking and selfpunishment. The results of these studies, combined with our study suggest that thought suppression is a goal that can be met in various ways (Rassin & Diepstraten, 2003).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These findings are in line with the results of a study by Rassin and Diepstraten (2003) who found a positive correlation between TCQ-punishment and WBSI-total in a sample of obsessive compulsive disordered patients. Nagtegaal and Rassin (2004) reached the same conclusion in a student sample and also established a relation between intrusive thinking and selfpunishment. The results of these studies, combined with our study suggest that thought suppression is a goal that can be met in various ways (Rassin & Diepstraten, 2003).…”
Section: Discussionsupporting
confidence: 63%
“…Independent sample t tests were conducted with the TCQ-subscales as test variables (for procedure, also see Nagtegaal & Rassin, 2004). Table 2 provides an overview of the results of these analyses.…”
Section: Thought Suppression and Thought Control Mechanismsmentioning
confidence: 99%
“…For instance, behaviors such as rumination and continued negative appraisal may perpetuate and intensify angry feelings, whereas perspective‐taking activity would tend to diminish anger intensity. A number of studies have also observed a particular association between high levels of hostility and aggression and avoidant coping styles (Nagtegaal & Rassin, 2004; Vandervoort, 2006). We suggest that while mindfulness cannot alter ‘‘wired‐in’’ responses to stimuli identified as threatening, it should attenuate avoidance behaviors and thus lay the groundwork for improving tolerance for negative emotions.…”
Section: Mindfulness and Emotion Repertoires: Mindful Relatingmentioning
confidence: 99%
“…TCAQ = Thought Control Ability Questionnaire a 0 Not included in the 95% confidence interval measures of impulsivity (Nagtegaal and Rassin 2004), thought suppression tendencies were also included in this second study to examine the links between this mental control technique, the four facets of impulsivity, and the different measures of intrusive thoughts. Only women took part in the second study because we wanted to control for gender effects and because the relations between lack of perseverance and unwanted intrusive thoughts may be closer in women than they are in men.…”
Section: Studymentioning
confidence: 99%
“…Nagtegaal and Rassin (2004), for example, examined the relations between impulsivity, thought suppression and intrusions in a Dutch student sample. In order to capture a wide range of impulsivity-related traits, these authors used three different measures: a preliminary version of the 11th revision of the Barratt Impulsiveness Scale (BIS-11a, Barratt 1994), the clinical scale Hypomania from the Minnesota Multiphasic Personality Inventory-2 (MMPI-2, Butcher et al 1989), and three subscales (impulsiveness, risk-taking, and sensation-seeking) from the Eysenck Personality Profiler (EPP, Eysenck et al 1996).…”
Section: Introductionmentioning
confidence: 99%